Inflation targeting as a monetary policy rule - Lars E. O. Svensson (Sveriges Riksbank, 1998)
The purpose of the paper is to survey and discuss ination targeting in the context of monetary policy rules. The paper provides a general conceptual discussion of monetary policy rules, attempts to clarify the essential characteristics of ination targeting, compares ination targeting to other monetary policy rules, and draws some conclusions for the monetary policy of the European System of Central Banks.
Keywords: E42; E52; 330